Корпоративная социальная ответственность как способ формирования идентичности персонала современных организаций - Горьковая, Ольга; Петров, Александр (Studia Sieci Uniwersytetów Pogranicza, 2020)
Goal – the article is devoted to the analysis of corporate social responsibility as a social, economic and legal phenomenon. The article presents the results of a theoretical and empirical sociological study of the features of the influence of organizational strategies of corporate social responsibility on the staff identity formation of companies and organizations in St.-Petersburg and the North‑West region of Russia. Research methodology – the authors argue that the development of ideas related to the need to create their own strategies for corporate social responsibility was significantly influenced by the practices of Western European firms and companies that began active cross‑border cooperation with Russian companies in the late XX – early XXI centuries. Score/results – the results of the study proved that socially responsible actions of Russian or foreign companies help to improve the internal organizational climate, improve the attitude of employees to their company and staff identity formation. Implementation of corporate social responsibility practices also solves complex organizational problems, for example, such as: increasing the level of staff loyalty and reducing staff turnover. Originality/value – the study showed that Russian companies are still lagging behind the West European companies in the field of creating and implementing effective corporate social responsibility strategies. But some examples show that Russian companies are already actively involved in the development of corporate social responsibility of a new, modern type.